Hubungan Indeks Massa Tubuh (IMT) dengan Derajat Keparahan Stroke Iskemik pada Pasien di Unit Penyakit Saraf RSUD Dr. Moewardi - Aga Suganda; . Suroto; Siti Utari (Nexus Kedokteran Klinik, 2013)
Background: Stroke is the third leading cause of death in the world. Approximately 80% of strokes are ischemic strokes. One of the significant prognostic factors causing morbidity of stroke patients is the Body Mass Index (BMI). National Institutes of Health Stroke Scale (NIHSS) is a systematic examination to determine the severity stroke. The aim of this study is to determine the relationship of body mass index (BMI) with ischemic stroke severity in patients at Neurology Ward Dr. Moewardi Hospital. Methods: This was an observational study with cross sectional analytic. A total of 32 subjects were selected by purposive sampling, they were ischemic stroke patients in the Neurology Ward Dr. Moewardi Hospital. Data were collected by direct interview, direct measurement of weight and height also examination of severity stroke patient by using NIHSS score. Data analysis used multiple logistic regression models and were processed with Statistical Product and Service Solutions (SPSS) 17.00 for Windows. Results: Multiple logistic regression showed OR = 17,690; CI 95% 1,190 263,039; and p = 0,037. These results have been earned by controlled the confounding variables of age, blood pressure, blood sugar levels, cholesterol levels and smoking history. Conclusions: Ischemic stroke patients with high BMI score has risk of ischemic stroke severity 17.690 times higher than whose normal BMI score.There is a strong relationship between body mass index (BMI) with the severity of ischemic stroke patients at Neurology Ward of Dr. Moewardi Hospital, the relationship is statistically significant in this study. Keywords:BMI, Stroke Severity, Ischemic Stroke